Formulasi dan Uji Stabilitas Sediaan Face Spray Ekstrak Etanol Daun Pepaya (Carica Papaya L.) - Adianti Putri Alitonang; Ikhsan H. Amir; Milda Milda (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Background: Papaya leaves (Carica papaya L.) contain various chemical compounds, such as alkaloids, which can cause a bitter taste and exhibit activity against Propionibacterium acnes, the bacteria responsible for acne or acne vulgaris. Objective: To determine the feasibility of papaya leaf ethanol extract as the main active ingredient in the formulation of a face spray and to assess the stability of different concentration variations in the ethanol extract face spray formulation. Methods: This study used an experimental method with varying concentrations of papaya leaf ethanol extract: F1 (8%), F2 (12%), and F3 (15%). Results: Organoleptic tests indicated that the formulations with ethanol extract concentrations of F1 (8%), F2 (12%), and F3 (15%) remained physically stable. The spray dispersion for each ethanol extract concentration—F1, F2, and F3—was 7 cm, 6 cm, and 6 cm, respectively, with a pH of 5. The findings demonstrated that the ethanol extract could be formulated as a face spray since it did not cause irritation, as confirmed by an irritation test on 10 respondents. Implications: The variations in papaya leaf ethanol extract concentrations—F1 (8%), F2 (12%), and F3 (15%)—met the established Indonesian National Standard (SNI).